Spirit Inovasi Pendidikan Islam dalam Slogan “Tempemu Tak Sehangat Tempeku” Studi Warung Mendoan Amba Suci Sotang - Sakir, Moh; Syam, Robingun Suyud El (Faidatuna, 2023)
Serious technological changes are taking place in the world and especially in the field of information and communication technology. These changes have had a significant impact on all aspects of people's lives and activities, including aspects of slogans. This article presents a detailed analysis of the spirit of innovation in Islamic education in the slogan "Tempemu Tak Sehangat Tempeku", where previous research has not been found. The research design used a quasi-experimental approach to the slogan of the mendoan amba Suci Sotang stall, in Sempor, Kebumen Regency. This study concludes that slogans have a significant influence on readers' perceptions. Islamic educational institutions must pay attention to slogans as part of educational innovation, for the sake of sustainable progress. This study does not invite readers to comment on slogans, but directs them to research findings that fill the gap in the field of Islamic education in creating slogans. Research implications, Islamic education researchers and practitioners can use this research to review the latest slogans of Islamic education institutions. This can also be useful for non-Islamic education researchers who are interested in multidisciplinary research settings. This research looks at the space of Islamic education studies in slogans by paying attention to contemporary literature and fresh perspectives.